2013
DOI: 10.1080/14681994.2013.808323
|View full text |Cite
|
Sign up to set email alerts
|

The associations among satisfaction with the division of housework, partner's perceived attractiveness, emotional intimacy, and sexual satisfaction in a sample of married or cohabiting Norwegian middle-class men

Abstract: Satisfaction with the division of housework has been shown to affect women's sexual satisfaction, but this relationship has rarely been studied in men. What are the relationships among men's satisfaction with the division of housework, their perception of their emotional intimacy with their partner, their perception of their partner's sexual attractiveness, and their sexual satisfaction? In the autumn of 2011, a selfselected online survey about men's sexual health was carried out in Norway, Croatia, and Portug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…Consistent with this, they found that increases in husbands' and wives' performance of non-traditional housework tasks were associated with decreases in sexual frequency, and for wives, sexual satisfaction. Although the actual division of housework was not found to predict husband's sexual satisfaction, research suggests that men's subjective assessment of the division of labor is central to their sexual satisfaction (Traeen, Štulhofer, and Carvalheira 2013).…”
Section: The Strains Of Egalitarianism? Relationship Stability and Sementioning
confidence: 94%
See 1 more Smart Citation
“…Consistent with this, they found that increases in husbands' and wives' performance of non-traditional housework tasks were associated with decreases in sexual frequency, and for wives, sexual satisfaction. Although the actual division of housework was not found to predict husband's sexual satisfaction, research suggests that men's subjective assessment of the division of labor is central to their sexual satisfaction (Traeen, Štulhofer, and Carvalheira 2013).…”
Section: The Strains Of Egalitarianism? Relationship Stability and Sementioning
confidence: 94%
“…They explained this by arguing that a traditionally gendered division of labor was necessary to enact the sexual scripts that lead to sexual arousal. Although the actual division of housework was not found to predict the husband’s sexual satisfaction, men’s subjective assessment of the division of labor is linked to their sexual satisfaction (Traeen, Štulhofer, and Carvalheira 2013).…”
Section: The Strains Of Egalitarianism? Relationship Stability and Sexual Intimacymentioning
confidence: 99%
“…Emotional Intimacy Scale. The Emotional Intimacy Scale, developed by Sinclair and Dowdy (2005), is a measure of romantic intimacy (see Murray & Hazelwood, 2011;Sˇtulhofer, Ferreira, & Landripet, 2014;Traeen, Sˇtulhofer, & Carvalheira, 2013). The measure contains five questions, such as "I can share my deepest thoughts and feelings with this person," rated on a seven-point Likert scale ranging from 1 (Strongly disagree) to 7 (Strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Tanto en la aproximación multidimensional como unidimensional y, tal como se observa en la literatura internacional en las últimas décadas, existe consenso en que el aspecto emocional de la intimidad es un componente fundamental de las relaciones de pareja, clave para el ajuste y bienestar psicológico, y característica esencial de una relación de pareja satisfactoria (Miller, 2015;Prager, 2014;Štulhofer et al, 2014;Traeen et al, 2013).…”
Section: Introductionunclassified
“…La EIE presenta ventajas en comparación a otras escalas que miden el mismo constructo, principalmente debido a su brevedad, fácil administración y a su foco en la intimidad emocional percibida en una relación cercana. Esto ha implicado su amplia y creciente utilización en investigación en los últimos años, incluyendo personas en pareja, con buenos índices de confiabilidad, la mayoría de las veces incluso más altos que en el estudio original y manteniendo la estructura propuesta (Amichai-Hamburger, & Etgar, 2016;Carvalheira & Costa, 2015;Guschlbauer et al, 2019;Hesse & Tian, 2020;Lonza et al, 2020;Carvalheira et al, 2014;Šević et al, 2016;Štulhofer et al, 2020;Traeen et al, 2013;Veit et al, 2016). Pese a su amplio uso, se desconocen estudios que confirmen la estructura factorial de esta escala.…”
Section: Introductionunclassified